Graduate employability in the Kingdom of Saudi Arabia: a future research agenda - Alwethainani, Mohammed H.; Mansor, Zuraina (Blue Eyes Intelligence Engineering & Sciences Publication, 2019)
In recent decades, a growing body of literature has emerged to illustrate the strong pressure on education institutions to prepare graduates for the world of work. This challenge has intensified since the expansion of higher education process that reframed the policy debate and placed the smooth transition from school-to-work and the employability of graduates at the forefront of education policy. In this scenario it is imperative to analyze the research trends in this area of research. The present study examined the research articles published in this area till 2018. The data was collected using the Scopus database to analyze the research trends in this area. The study findings have clearly highlighted that majority of the research in the field of employability is conducted in developed countries and this area of study is under explored in Kingdom of Saudi Arabia. The findings also showed that the research related to the factors contributing towards Saudi graduates’ employability is one area which needs to be studied.